Theoretical and experimental study of a novel compressor - Shakya, Pradeep (Nanyang Technological University, 2020)
Many different types of the positive displacement rotary compressors are currently used in air-conditioning, refrigeration and heating applications. According to Japanese Air-conditioning and Refrigeration News, the production for positive displacement rotary compressors in 2018/19 alone exceeded 200 million pieces. Obviously, large amount of materials, especially metal such as steel, are being used every year to produce these compressors. Saving these materials will lead towards a more sustainable environment. This thesis investigates the development of a novel compressor, namely, Coupled Vane Compressor, which is significantly material saving, and to our knowledge, it is one of the most compact rotary vane compressors. Coupled Vane Compressor (CVC) as the name suggests, has two vanes coupled together. Its unique feature is that the coupled vanes cut diametrically through the rotor. Hence, the design of CVC, theoretically, requires the rotor to be as small as the motor shaft for it to work. Due to its compact design, CVC has the potential in saving a significant amount of material during its production and thus leading to smaller carbon footprint over its lifecycle compared to the existing rotary compressors. The mathematical models of CVC were formulated to study its operational characteristics. The mathematical models developed for the studies include the mathematical representations of the geometry of its working chamber, thermodynamics of the working fluid, main flows through the inlet and outlet ports, secondary flows through internal leakages, kinematics and dynamics of the moving parts and lubrication of the rubbing parts. A simulation program was developed in Fortran and the program included the mathematical models developed to predict the performance of CVC. REFPROP was used to calculate thermodynamic properties of the working fluid. Moreover, parametric studies of CVC were performed, and the performance of CVC for various vane material, operating pressure ratio and rotor-to-cylinder radii ratio were studied. The results obtained showed that, for steel vanes, CVC can operate at the minimum speed of 1000 r min-1 and minimum pressure ratio of 2 without vane chattering. Using aluminium vanes, which is lighter than steel vanes, the frictional losses at the vane tips was reduced and thus the improvement of over 3% in mechanical efficiency was predicted. For simplicity and to save costs, an open-type test circuit was designed using air as the working fluid to experimentally test the CVC prototype. The CVC prototype was designed to have the maximum suction chamber volume of 44 cm3. The measured parameters include the discharge pressure, temperature and the flowrate. At 1500 r min-1, the pressure ratio of 6.1 was measured. The predicted results were then compared with the measured data to validate the mathematical models developed. The comparison showed the maximum discrepancy of 15% between the predicted results and the measured results.